2004
DOI: 10.1144/0016-764904-015
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ramps and thrust terminations: an example from the Moine Thrust Zone, NW Scotland

Abstract: Detailed remapping within the Assynt Culmination in NW Scotland shows that the Ben More Thrust joins the Glencoul Thrust along a lateral branch line positioned in Loch Glencoul. This branch line marks the northern lateral termination of the Glencoul Thrust. The thrust on the northern shore of Loch Glencoul (‘the famous view’) is thus the Ben More Thrust. The Ben More Thrust Sheet is therefore much larger than previously thought. The lateral terminations of the Ben More Thrust to the north and the south are of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…For instance, one remaining problem was the northern termination of the Ben More Thrust, as discussed in Elliot & Johnson (1980) and ; another problem was the southern continuation of the Glencoul Thrust near Inchnadamph, with different solutions proposed by Bailey (1935), Christie (1963) and Elliot & Johnson (1980). Coward (1982) suggested the existence of large-scale 'surge-zones' involving linkage between frontal thrusts and extensional faults at the rear as a solution, a model rejected by Krabbendam and Leslie (2004).…”
Section: History Of Researchmentioning
confidence: 99%
“…For instance, one remaining problem was the northern termination of the Ben More Thrust, as discussed in Elliot & Johnson (1980) and ; another problem was the southern continuation of the Glencoul Thrust near Inchnadamph, with different solutions proposed by Bailey (1935), Christie (1963) and Elliot & Johnson (1980). Coward (1982) suggested the existence of large-scale 'surge-zones' involving linkage between frontal thrusts and extensional faults at the rear as a solution, a model rejected by Krabbendam and Leslie (2004).…”
Section: History Of Researchmentioning
confidence: 99%
“…As deformation progressed, and the nappe pile cooled, deformation in the Assynt sector propagated forward again, resulting in the classic semi-brittle thin-skin thrusting in the Assynt Culmination (e.g. Elliott & Johnson 1980;Coward 1985;Krabbendam & Leslie 2004. This brittle movement was probably responsible for the brittle movement along the Southern Moine Thrust as seen at Knockan Crag.…”
Section: Tectonic Evolutionmentioning
confidence: 99%
“…The Moine Thrust Zone varies from a relatively simple planar structure to a complex array of interconnected thrust sheets (Plate 1A; Krabbendam and Leslie, 2004). Detailed analysis has shown that the thrusts generally developed in a forelandpropagating sequence, with successively younger and lower thrusts transporting older and higher thrusts to the WNW in 'piggyback' fashion (Elliott and Johnson, 1980;McClay and Coward, 1981;Butler, 1982).…”
Section: The Greenland Caledonides -Evolution Of the Northeast Marginmentioning
confidence: 99%